Technical Guidance on Raising Superior Local Chickens in Alebo Village, Konda Subdistrict South Konawe Regency - Zulkarnain, Deki; Rusdin, Muh.; Astarika, Rina; Indi, Amiluddin; Hadini, Hairil A.; Aku, Achmad Selamet; Pagala, Muhammad Amrullah; Libriani, Restu; Yaddi, Yamin; Jabudin, La Ode; Dewi, Fitria (CV. Literasi Indonesia, 2024)
This service program aims to increase the knowledge and skills of partner breeders regarding feed formulation techniques using local raw materials and superior local chicken breeding techniques using automatic hatching machines as well as seed production systems intensively and semi-intensively raised. The implementation of this service program uses group and individual counseling methods, which include non-physical and physical activities. Non-physical activities take the form of theoretical counseling using lecture and discussion methods. In contrast, physical activities are carried out using demonstration methods and field visits related to feed formulation techniques using local raw materials and superior local chicken rearing techniques using automatic hatching machines and intensive and semi-intensive seed production systems. The results of the implementation of this service program showed that the technical guidance activities for raising superior local chickens, which were carried out in Alebo Village, Konda District, South Konawe Regency, received a positive and enthusiastic response from the local village government and partner breeders. This technical guidance activity for raising superior local chickens that combined non-physical activities in the form of theoretical counseling with lecture and discussion methods with physical activities in the form of demonstrations and field visits can be a solution to problems experienced by partner breeders. Implementation of this service program is effective in increasing the knowledge and skills of partner breeders regarding feed formulation techniques using local raw materials and superior local chicken raising and breeding techniques using automatic hatching machines as well as seed production systems intensively and semi-intensively raised.